2021
DOI: 10.1371/journal.pone.0257986
|View full text |Cite
|
Sign up to set email alerts
|

Does nicotine exposure during adolescence modify the course of schizophrenia-like symptoms? Behavioral analysis in a phencyclidine-induced mice model

Abstract: The first symptoms of schizophrenia (SCHZ) are usually observed during adolescence, a developmental period during which first exposure to psychoactive drugs also occurs. These epidemiological findings point to adolescence as critical for nicotine addiction and SCHZ comorbidity, however it is not clear whether exposure to nicotine during this period has a detrimental impact on the development of SCHZ symptoms since there is a lack of studies that investigate the interactions between these conditions during this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 112 publications
(139 reference statements)
0
1
0
Order By: Relevance
“…The higher number of potential protein markers of PCPNIC combined insults when compared to protein markers of SCHZ and NIC further corroborates this conclusion. Nevertheless, this study also identified a shared impact of phencyclidine and nicotine history, which supports evidence of interactive events between SCHZ and nicotine misuse in patients and comparable effects in animal models [55,61,62]. Consistent with this finding, despite the identification of proteins exclusively deregulated in the PCPNIC group, the top Reactome pathways were shared with other experimental groups.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The higher number of potential protein markers of PCPNIC combined insults when compared to protein markers of SCHZ and NIC further corroborates this conclusion. Nevertheless, this study also identified a shared impact of phencyclidine and nicotine history, which supports evidence of interactive events between SCHZ and nicotine misuse in patients and comparable effects in animal models [55,61,62]. Consistent with this finding, despite the identification of proteins exclusively deregulated in the PCPNIC group, the top Reactome pathways were shared with other experimental groups.…”
Section: Discussionsupporting
confidence: 84%
“…These include hyperactivity in the mesolimbic dopaminergic system and hypoactivity in the mesocortical one, as well as hypofunction in the cortical glutamatergic and gamma aminobutyric acid (GABA) systems [50,52,54]. Most importantly, phencyclidine-induced SCHZ-like behavioral deficits were recently also demonstrated to occur when administration occurs during adolescence [55]. As for nicotine exposure, a subcutaneous osmotic minipump is an established model that has the advantage of being less stressful than other routes of administration, in addition to allowing for a constant dose and a controlled period of administration [56,57].…”
Section: Introductionmentioning
confidence: 99%
“…Both acute and subchronic PCP injections at different doses cause various behavioral deficits in animals relevant to human schizophrenia symptoms, such as impairments in memory and learning [ 45 , 46 ], sociability [ 47 , 48 ], locomotor activity [ 49 ], and sensorimotor gating measured in PPI [ 50 ]. Notably, some studies have failed to confirm important features of schizophrenia-like behavior in rodents [ 47 ], indicating that the effects of PCP in behavioral studies may differ depending on the dose used and the administration paradigm.…”
Section: Pharmacological Modelsmentioning
confidence: 99%